EFFECT OF SYSTEMIC BETA-BLOCKERS, ACE INHIBITORS, AND ANGIOTENSIN RECEPTOR BLOCKERS ON DEVELOPMENT OF CHOROIDAL NEOVASCULARIZATION IN PATIENTS WITH AGE-RELATED MACULAR DEGENERATION. Issue 10 (October 2015) - Thomas, Akshay S.; Redd, Travis; Hwang, Thomas
Abstract : Purpose: Recent studies have suggested that the use of systemic beta-blockers, angiotensin-converting enzyme inhibitors, and angiotensin receptor blockers can induce regression of choroidal neovascularization in rodent models. The purpose of this study is to evaluate if these agents have a protective effect against the development of choroidal neovascularization in patients with age-related macular degeneration. Methods: In this single-center retrospective case–control study, the charts of 250 patients with neovascular age-related macular degeneration were compared with those of 250 controls with dry age-related macular degeneration. Charts were reviewed for current and past use of beta-blockers, angiotensin-converting enzyme inhibitors, and angiotensin receptor blockers. Frequency tables were generated, and associations were examined using chi-square tests, t -tests, and multivariate logistic regression. Results: There was no statistically significant difference between rates of beta-blocker use ( P = 0.57), angiotensin-converting enzyme inhibitors use ( P = 0.20), or angiotensin receptor blockers use ( P = 0.61) between the 2 groups. Additionally, there was no statistically significant difference between rates of use of combinations of the above drugs between the two groups. Conclusion: Although there is growing evidence that beta-blockers, angiotensin-converting enzyme inhibitors, and angiotensin receptor blockers can induce regression of choroidal neovascularization in rodent models, these medications do not seem to confer a protective effect against the development of choroidal neovascularization in patients with age-related macular degeneration. Abstract : There is growing evidence that beta-blockers, angiotensin-converting enzyme inhibitors, and angiotensin receptor blockers can induce regression of choroidal neovascularization in rodent models. In this study, the authors examine the effect of these systemic medications on the development of choroidal neovascularization in age-related macular degeneration patients.